A experiência do cliente está na sua mão: estudo do aplicativo da marca Renner com base no conceito de ux design - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Application development is a recent technology that makes it possible to narrow the presence of brands with their consumers through smartphones on mobile platforms. The online sales that were previously concentrated only on the websites developed by the brands, now suffer a great fit for the mobile medium. So the problem issue of this study is: how is the retailer Renner using its application in the experience of its customers with the brand? The overall goal of the survey was to see how Renner's retail brand is using its application in the experience of its customers with the brand. As for the methodology, the descriptive research was used, with the qualitative-quantitative approach, the data collection was from the image capture through the print screen of the Renner application data and the systematic observation of the social networks, platform app store and application and to describe and interpret the content was used the methodology of content analysis. The concept of UX Design is the relationship of a product, service or environment that provides a satisfying experience for someone who uses them. The UX is branched into sub concepts that form the central concept, which are, visual design (aesthetics), information architecture, interaction design, usability, user search, data analysis. It was obtained as a result of the proposed objectives, that the brand adapted to the digital medium with good strategies, such as exclusive promotions for the app, improvement of new versions and functionalities, and a user-centered view, a prime factor of good experience in However, this experience is affected by the low incorporation of this system in servers that carry greater data flow and low development of application adequacy for different models of smartphones. We conclude that the brand is using its application properly and carefully because it is a recent technology and in test, the brand for the moment makes the communication directed to the site, but implements the mobile technology developing in each new version a new function that incorporates in its system to build and instigate new pleasant experiences with the Renner brand. In this way the study contributes to the questioning about the use of an application by a particular brand, a service or even a non-commercial use, considering that this new technology is vast and covers several areas of action to develop together to the future of the mobile.
Keywords: Vendas; Aplicativos móveis; Comércio eletrônico; Renner (Firma); Sales; Mobile Apps; Commerce; CNPQ::CIENCIAS SOCIAIS APLICADAS